Boron rich solids sensors, ultra high temperature ceramics, thermoelectrics, armor - Orlovskaya, Nina.; Lugovy, Mykola; SpringerLink (Online service). (Dordrecht Springer, 2011)
Theobjective of this book is to discuss the current status of research and development of boron-rich solids as sensors, ultra-high temperature ceramics, thermoelectrics, and armor. Novel biological and chemical sensors made of stiff and light-weight boron-rich solids are very exciting and efficient for applications in medical diagnoses, environmental surveillance and the detection of pathogen and biological/chemical terrorism agents. Ultra-high temperature ceramic composites exhibit excellent oxidation and corrosion resistance for hypersonic vehicle applications. Boron-rich solids are also promising candidates for high-temperature thermoelectric conversion. Armor is another very important application of boron-rich solids, since most of them exhibit very high hardness, which makes them perfect candidates with high resistance to ballistic impact. The following topical areas are presented: boron-rich solids: science and technology; synthesis and sintering strategies of boron rich solids; microcantilever sensors; screening of the possible boron-based thermoelectric conversion materials; ultra-high temperature ZrB2 and HfB2 based composites magnetic, transport and high-pressure properties of boron-rich solids; restrictions of the sensor dimensions for chemical detection; armor.
Contributing Authors -- Preface -- Acknowledgment -- Boron Carbide/Boron Carbide - Carbon Nanofibers Laminates with Weak Interfaces -- All Ceramic Cantilever Sensors With Boron Carbide Layer: Advantages And Dimensional Limitations; M. Lugovy -- Raman Effect In Boron And Boron-Rich Compounds -- Experimentally Founded Charge Transport Model For Icosahedral Boron-Rich Solids -- Magnetic And Thermoelectric Properties Of Boron-Rich Solids -- Scratch Studies in Boron-Rich Lightweight and Ultrahigh Temperature Ceramic -- The Electronic Properties Of Metal Borides And Borocarbides. Differences And Similarities.-Investigation of Hard Boron-rich Solids: Osmium Diboride and -rhombohedral Boron -- Elastic and Vibration Properties of Boron Carbon Ultra Hard Materials -- Processing and Properties of Ultra-refractory Composites Based on Zr- and Hf-borides: State of the Art and Perspectives -- Behavior of Boron Doped Graphites and Boron Carbide under Ion Beam and Plasma Irradiation.-Vibrational Spectroscopy of Adsorbates on the (111) and (100) Surfaces of Lanthanum Hexaboride -- Zirconium Dodecaboride, a Novel Superconducting Material with Enhanced Surface Characteristics -- Boron under Pressure: Phase Diagram and Novel High-pressure Phase -- Behavior Of The Crystalline Boron Carbide Coating Under Tokamak Conditions -- Electron Structure, Transport, and Superconducting Properties of ZrB12, ZrB2, YB6 and MgB2 -- Densification, Microstructure Evolution and Mechanical Properties of Ultrafine SiC Particle - Dispersed ZrB2 Matrix Composites -- Mechanochemically Driven Syntheses of Boride Nanomaterials.-Vibrational Properties Of Zr(Hf)B2-Sic Uhtc Composites By Micro-Raman Spectroscopy -- Synthesis and Sintering Strategies of Boron-Rich Solids -- Field-Assisted Densification Of Superhard B6o Materials With Y2o3/Al2o3 Addition.
Electronic reproduction.
Keywords: Nonmetallic materials; Solid state physics; Solid state chemistry; Boron; Electronic books